Roles and contribution of brokers (middlemen) and perceptions towards the custom farming system in the Muda area, Malaysia - Man, Norsida; Mat Zain, Nasiha (Asian Network for Scientific Information, 2014)
Custom farming, or the custom hiring system, has long been widely practiced in paddy farming in the Muda area of Malaysia. The objective of the system is to provide farmers with machinery such as harvesting equipment, tractors and lorries for convenience. Brokers, or middlemen, within the system act as intermediaries between the farmers and service providers, who are the owners of the machines, tractors and lorries. This study aims to examine the profile of these brokers, in terms of their years of experience as a broker, the size of land under their supervision, the agreement method between farmers and service providers and also broker contributions to farmers. The research is carried out in the context of paddy farming in the Muda area. The respondents consist of 35 brokers and 65 farmers, each of whom completed a questionnaire. The data is analyzed using SPSS. The results show that through contributions of brokers within this custom farming system, problems relating to the ownership of machinery, lack of time and energy and farmers’operating costs can be reduced. However, there are still weaknesses in this service system that needs to be improved.